The International Bank Lending Channel of Monetary Policy Rates and QE: Credit Supply, Reach‐for‐Yield, and Real Effects - MORAIS, BERNARDO; PEYDRÓ, JOSÉ‐LUIS; ROLDÁN‐PEÑA, JESSICA; RUIZ‐ORTEGA, CLAUDIA (Journal of Finance, 2019)
ABSTRACT We identify the international credit channel by exploiting Mexican supervisory data sets and foreign monetary policy shocks in a country with a large presence of European and U.S. banks. A softening of foreign monetary policy expands credit supply of foreign banks (e.g., U.K. policy affects credit supply in Mexico via U.K. banks), inducing strong firm‐level real effects. Results support an international risk‐taking channel and spillovers of core countries’ monetary policies to emerging markets, both in the foreign monetary softening part (with higher credit and liquidity risk‐taking by foreign banks) and in the tightening part (with negative local firm‐level real effects).